Achilles Tendon Adaptation to Neuromuscular Electrical Stimulation: Morphological and Mechanical Changes - Létocart, Adrien; Grosset, Jean-Francois (International Journal of Sports Medicine, 2020)
It remains unclear whether neuromuscular electrical stimulation can induce sufficient tendon stress to lead to tendon adaptations. Thus, we investigated the effect of such a training program on the triceps surae muscle following the morphological and mechanical properties of the Achilles tendon. Eight men participated in a 12-week high-frequency neuromuscular electrical stimulation training program of the triceps surae muscle under isometric conditions. Ultrasonography was used pre- and post-intervention to quantify cross-sectional area, free length, and total length of the Achilles tendon, as well as the myotendinous junction elongation during a maximal isometric ramp contraction under plantar flexion. Neuromuscular electrical stimulation training does not lead to changes in Achilles tendon free and total length, cross-sectional area, or maximal elongation capacity. However, a significant increase was evidenced in maximal tendon force post-training (+25.2%). Hence, Young’s Modulus and maximal stress were significantly greater after training (+12.4% and +23.4%, respectively). High-frequency neuromuscular electrical stimulation training induces repeated stress sufficient to lead to adaptations of mechanical properties of the Achilles tendon. Thus, this training technique may be of particular interest as a new rehabilitation method in tendinopathy management or to counteract the effect of hypo-activity.
Keywords: neuromuscular electrical simulation; achilles tendon; triceps surae; training